Do formal para o informal: executivos em trabalhos flexíveis - Kim, Han Na (2008)
When we observe the present work in the world, we can notice a move towards the direction of greater flexibility in regards to formal employees and workers that act through flexible forms of labor contracts. The flexible employment contract refers to the contract that does not follow the formal model of labor contract, governed by CLT (Consolidation of the Labor Laws), and, has been studied lately as a result of changes in the workplace organization, usually associated with the search of more productive and cheaper workers. Due to the enlargement of the involved phenomena of these transformations, we delimited the subject and the public to be studied: adopting the idea of social construction of reality, from Berger and Luckmann (1966/2002), we analyzed the 'migration' processes of 30 executives, residents of São Paulo city, ex-employees of large corporations, that had experiences in high and middle management at multinational and national organizations, and, at present, work in the markets under flexible labor contracts. For our study, we understand that the executives are formal workers that occupy positions of high and middle management in the organizational hierarch and have the power of decision and prestige. Being so, the objective of this study is to describe the sense attributed by executives, to the 'migration' process to more flexible forms of work and to the new reality lived in the workplace. The research follows a qualitative approach, utilizing semi-structured in-depth interviews to gather the information; for the interview analysis, we used, as the basis, the ideas of speeches practices from Spink and Medrado (1999/2004). The constructionist perspective permitted to verify that executives in flexible workplaces possessed high level of selfconfidence, a missionary vision of his/her work, and different motives for the 'migration'. Through their statements we can observe the survival strategies and how to become successful as a flexible worker; the interviewees perceptions of the Brazilian market; the change in customer relationships, the family and the personal network. Despite the problems faced to settle in, the majority want to continue with flexible work, even though a large number of studies have shown that flexible labor contracts as a factor that make workers’ lives more precarious. For the executives in flexible employment, life as a formal CLT worker is a thing of the past: now, they need to show themselves as competent at any cost, plan themselves for the 'dry spells' improve their network, increase their knowledge and to spend time with their family. The motives to stay are diverse, but all possesses a conversion point: the sensation that they dominate their own lives, time, money, knowledge, and future. Perhaps, many situations will present themselves in daily life to give in to the customer and greater dedication than a formal employee; but, in the 'everyday reality', the sensation is that they are the 'owner' of their lives.